Production of monoclonal antibodies against conserved components of infectious bronchitis virus - Souza,C.M. (2001)
Murine hybridomas producing IgG1 monoclonal antibodies (Mabs) against N and S2 proteins (53KDa and 82KDa, respectively) from avian infection bronchitis virus (IBV) strain M41 were generated by the fusion of a myeloma cell line (Sp2/0-Ag14) with spleen cells from Balb/c mice previously immunized with whole virus IBV M41. Post-fusion screening criterion was by ELISA and 36 positive hybrids were generated after fusions. Two hybrids specific to N (N3F10) and S2 (S12B2) proteins from M41 (serotype Massachusetts) were selected by western blotting. These Mabs recognized the Ark-99 (serotype Arkansas) and A5968 (serotype Connecticut) IBV strains in addition to M41. By ELISA, the Mab against the S2 (S12B2) recognized all reference and Brazilian strains (M41, SE-17, H52, 297, 283, PM-1, PM-2, PM-3, 351, 29-78 E 327) studied, while the Mab against N recognized only six (M41, SE-17, H52, 283, 327 e 297) strains. The Mab against S2 may become a useful tool for IBV detection on the routine diagnosis of infectious bronchitis, especially for helping the differential diagnosis of clinically and pathologically confusing diseases, while the Mab against N (N3F10) recognized a probably less conserved region among the strains and may be interesting to comparing IBV isolates.